Knowledge and perceptions toward cardiology pharmacy education and training: Malaysian pharmacy students’ perspectives - Elnaem, Mohamed Hassan Abdelaziz; Che Ibrahim, Muhammad Zakirin; Abdul Rahman, Nor Akhi Hijriyati; Mahyidin, Nurul Haziqah; Sulaiman, Nurliyana Mahirah; Zulkiflee, Farah Ameliana (Elsevier, 2018)
Introduction The role of pharmacists in the patient care process is developing in the Malaysian healthcare setting. Pharmacy students are required to be aware of cardiology pharmacy practice as this is one of the top national disease burdens in Malaysia. This study was conducted to assess the knowledge and perceptions of pharmacy students toward the cardiology pharmacy specialty practice.